Software Code Refactoring: A Comprehensive Review - hiba Al-shakarjy; Dujan Basheer Taha (College of Education for Pure Sciences, 2023)
The complexity of software has increased because of the development as well as the difficulty of requirements during the development of software, or to add new features that eventually lead to reduce the quality of the software as a whole. Software refactoring can be defined as included processes in the maintenance period of a software life cycle, and it is a technique to clean the software code from code bad smell and to improve the internal structure of the software, in addition to increasing the quality of software by using a set of activities without changing the external behavior of a software. Researchers have been developing techniques to reform software during the code or design standard to decrease the effort and time required for maintenance processes. This paper provides a systematic review of the literature for 17 studies of code standards, An automatic search is utilized in the digital libraries to look for the relevant studies that were published from 2014 to 2021, the best five researchers are chosen in this subject, five studies or less are chosen for each depending on the number of reference in the database of scientific sites, or using an approach or a new method to get good results. Eventually, each paragraph is analyzed and mentions the method or algorithm used in rebuilding software, further the aims, and the result for each paper.